(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3aj GdWQjb Yed HGdXf aj GdGeJKGd GdhGbYj, bhdg Tchc daQV Cf GdEeGQI de Jcf eXfhfI Hd cGfJ eSdhcI GdGYJHGQ Ch ehgheI GdGYJHGQ adeG jchf GdYeds
(3BNQgG (B:s
(3BNQgG(B: (3hgh GdPj GSJaGOg ef GdCNHGQ hYHQ Yfg Hbhdg hHGdLedI, bhdg aj TQM GdEQTGO, Cj eLdi Yf cdGeg GdehLhO aj TQM GdEQTGOs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs